Domestic Philosophy of Law as an Ideological Prerequisite of a Philosophical Type of Understanding of Law - Vladimir Valentinovich Kozhevnikov; Anastasia Evgenievna Cherednichenko (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2019)
This scientific article is based on the analysis of some,           from our point of view, basic provisions of the textbook for masters by the famous Russian scientist, professor Martysciin Orestes Vladimirovich "Philosophy of the law". The purpose of the article is to prove scientific character the Philosophy of the Law against the background of the contrary statements of philosophers and lawyers-theorists about its not scientific nature; to consider Philosophy of the Law as an ideological prerequisite of philosophical type of understanding of the right and to analyses the last. For the achievement of this purpose the following tasks were set: 1) to analyses various arguments of the scientists who are not recognizing the scientific nature of Philosophy of the Law, considering it as a method of the human relation to the world; 2) to consider views of the scientists giving to the Philosophies of the Law the status of science; 3) to show features of philosophical type to which it is not given in science of due attention; 4) to critically evaluate positions of those scientists who unreasonably identify moral (natural and legal) and philosophical types of understanding of the law; 5) to show distinction of moral (natural and legal) and philosophical types of understanding of the law. The result of the article's research are the provisions: 1) the legal philosophy is to be considered as the independent science having the subject, methodology, performing the specific functions, corresponding to other both legal, and social sciences; 2) the Philosophy of the Law is an ideological prerequisite of philosophical type of understanding of the law which defines the sphere or border of a measure of freedom of the person. In conclusion it is to emphasize that joint efforts of lawyers, philosophers, representatives of other social sciences concerning this subject area and a subject matter are necessary for overcoming the existing disagreements on the matters of principle concerning Philosophy of the Law, and for the decision, arising in the course of its development and improvement of problems.